2006
DOI: 10.1029/2006gl027185
|View full text |Cite
|
Sign up to set email alerts
|

Calculated and observed climate change in the thermosphere, and a prediction for solar cycle 24

Abstract: [1] The long-term change of thermospheric neutral density has been investigated using satellite drag measurements and through sensitivity studies using upper atmosphere general circulation models. The magnitude of the change has been quantified in both approaches, and the source of the secular change attributed to the concentration changes of greenhouse gases. In this study, we use CO 2 concentration measured at Mauna Loa Observatory and solar variation based on a proxy model to calculate the secular change of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
85
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 22 publications
16
85
0
Order By: Relevance
“…These observational findings are qualitatively consistent with modeling results by Roble and Dickinson (1989). Using CO 2 concentrations measured at Mauna Loa, Qian et al (2006) calculated neutral density trend for the period from 1970 to 2000, and found an average density trend of −1.7%/decade at 400 km. Model simulations also showed that this density trend corresponds to a neutral temperature trend of −5.4 K for this three decades at 400 km.…”
Section: Long-term Trendssupporting
confidence: 77%
See 2 more Smart Citations
“…These observational findings are qualitatively consistent with modeling results by Roble and Dickinson (1989). Using CO 2 concentrations measured at Mauna Loa, Qian et al (2006) calculated neutral density trend for the period from 1970 to 2000, and found an average density trend of −1.7%/decade at 400 km. Model simulations also showed that this density trend corresponds to a neutral temperature trend of −5.4 K for this three decades at 400 km.…”
Section: Long-term Trendssupporting
confidence: 77%
“…Model simulations also showed that this density trend corresponds to a neutral temperature trend of −5.4 K for this three decades at 400 km. Figure 9 shows altitude profiles of the temperature trend and neutral density trend from 1970 to 2000, from the model simulations of Qian et al (2006).…”
Section: Long-term Trendsmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of decrease in density at 400 km has been estimated to range from 2% to 5% per decade at solar maximum and minimum, respectively [Emmert et al, 2004[Emmert et al, , 2008. Modeling work places a slightly lower estimate on the thermospheric density decline of typically 1% to 2% per decade at 400 km [Qian et al, 2006]. The cause of this contraction is linked to the long-term increases in CO 2 concentration, which have resulted in warming of the troposphere.…”
Section: Introductionmentioning
confidence: 99%
“…This measured lower EUV irradiance combined with the modeled effects, e.g. due to the amount of CO 2 in the Earth's atmosphere (Roble and Dickinson, 1989;Qian et al, 2006) caused McIntosh, 2009) the proposed approach may be used to explore how the change in the spatial scale of the TR network affects the Earth's thermosphere.…”
Section: Introductionmentioning
confidence: 99%